Stabilization and synchronization of 5-D memristor oscillator using sliding mode control. (17th November 2018) - Mufti, Muhammad Rafiq; Afzal, Humaira; Rehman, Fazal-ur-; Ahmed, Nisar
ABSTRACT: This article presents a control design method for asymptotic stabilization, synchronization, and antisynchronization of a five dimensional chaotic memristor oscillator system. Two cases are considered: (i) with known parameters, (ii) and with unknown parameters. When a system's parameters are known, then controllers are designed using sliding mode approach and when system's parameters are unknown then controllers are devised using adaptive integral sliding mode control method. Hurwitz surfaces are constructed in both approaches. To employ the integral sliding mode, firstly, the system is transformed into a special structure containing a nominal part and some unknown terms computed adaptively. Then, the system is stabilized using integral sliding mode control. The stabilizing controller, consisting of the nominal control plus some compensator control, is then designed. The compensator controller and the adapted laws are derived in such a way that the time derivative of a Lyapunov function becomes strictly negative. The effectiveness of the proposed scheme is tested through computer simulation.